A Case of Von Hippel–Lindau Disease with Bilateral Pheochromocytoma and Ectopic Hypersecretion of Intact Parathyroid Hormone in an Adolescent Girl - Rym Belaid; Ibtissem Oueslati; Melika Chihaoui; Meriem Yazidi; Wafa Grira; Fatma Chaker (Case Reports in Endocrinology)
Von Hippel–Lindau disease is an autosomal dominant inherited syndrome predisposing to a variety of highly vascularised tumors in different organs. Although bilateral pheochromocytoma was reported in patients with von Hippel–Lindau disease, the coexistence of primary hyperparathyroidism is not a common condition. We report an observation of a primary hyperparathyroidism secondary to an ectopic secretion of intact parathyroid hormone in a 17-year-old girl with von Hippel–Lindau disease and bilateral pheochromocytoma. She presented with a newly diagnosed diabetes mellitus and a severe arterial hypertension. Blood tests disclosed hypercalcemia with increased intact PTH level. Cervical ultrasound and sestamibi scintigraphy were normal. Twenty-four-hour urinary normetanephrine level was highly elevated pointing to a catecholamine-secreting tumor. The abdominal computed tomography showed bilateral adrenal masses. MIBG scintigraphy exhibited a high accumulation of the tracer in both adrenal tumors. Genetic testing revealed a mutation of the VHL gene. The patient underwent a bilateral adrenalectomy. The postoperative outcome was marked by normalization of blood pressure, blood glucose, calcium, and PTH levels. In our case, the elevation of intact PTH and its spontaneous normalization after surgical treatment of pheochromocytomas confirms its ectopic secretion.